GERABAH SITUS MANSINAM KAJIAN ETNOARKEOLOGI - Fairyo, Klementin (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
The Process of vessels making in Mansinam site was not far too different with other places in Indonesia: using clay as the basic material. The vessel making was a woman’s work, started from clay gathering to firing process. Based on the observation of the edge shape, it is predicted that the vessels found in Mansinam Island belongs to the type of pot. The observation on the core shows that on the process of making, the firing was opened and not spread evenly. Pot was used for cooking and keeping food. The vessels from Mansinan Island has spread vast through trade and barter to Wandamen coastal area, Biak Numfor islands, Bird’s Head Peninsula coastal areas and Raja Ampat Islands.